Linearlydeteriorating EOQmodel for imperfect items with price dependent demand under different fuzzy environments - Suchitra Pattnaik, Mitali Madhusmita Nayak, Milu Acharya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, linearly deteriorating EOQ models have been developed for imperfect quality items (both crisp and fuzzy models) with linear and price dependent demand. The price depended demand is considered as two different types of fuzzy number viz. trapezoidal and cloudy fuzzy model. Defuzzification has been done using signed distance method and Yager‘s Ranking Index. All results are verified numerically and graphically for both models. Sensitivity analysis of the model is carried out to validate the models for optimality.